Penerapan Teknologi Virtual Reality Pada Property Perumahan - Robert Saputra; Subari; Saiful Yahya (Prosiding SISFOTEK, 2021)
Virtual Reality presents high technology that can provide a virtual feel like what happens in real life with good graphic quality to complement traditional methods in terms of performance and product. In its development, Virtual Reality (VR) is also implemented in the property industry, both as a medium for property product promotion services and as a simulation medium for users to surf in the virtual world, getting to know the property products offered without having to visit the actual location. To market and sell products, most property businesses still use brochures in marketing and selling products. So it costs more and takes a lot of time. This research starts from the planning stage, collecting information and data needed in the design, and building the system by analyzing the application that includes the needs or requirements related to what will be developed. the next stage is to design the assets needed in making the application and then try it out. This research produces Virtual Reality application as a marketing multimedia in property business that can present complete information by presenting reality in virtual form. Virtual-Reality applications can be used to make it easier to market and sell products, able to provide detailed information so that it is easier for potential buyers to get information, view visuals and choose the desired product virtually. The results of the questionnaire that have been filled out by the user, the conclusion from the research on the application of VR Perumahan is in the "Very Positive" category with a total percentage of 223 which is between 195 to 240.